Modificação superficial do tecido de malha de ácido polilatico (PLA) por tratamento plasma - Cruz, Luciani Paola Rocha (2013)
Some fibrous materials, for having properties such as biocompatibility, strength and flexibility, are of great interest for medical and pharmaceutical applications. Among these materials, the fabric made from polylactic acid (PLA) has received special attention, and beside to present these features, is derived from biological source, antimicrobial and bioabsorbable. One of the limitations of PLA is its low wettability and capillarity. Due to this, it is necessary to perform surface modification of the knitted fabric, increasing its hydrophilicity. This work aims to realize the plasma treatment at low pressure in order to increase the surface energy of the polymer. The work was divided into three steps: i) Influence of the gas ratio (oxygen and nitrogen) in the surface modification of PLA fabric after the plasma treatment, ii) physical characterization and physicochemical surface tissue; iii) Evaluation of the effect from current and gas ratio in the capillary rise of tissues and iv) Study of capillarity in yarns and fabrics. The results showed that better gas ratios were the atmospheres: 100% oxygen; 100% nitrogen and 50% oxygen and 50% nitrogen. The surface characterization showed changes in topography and introduction of polar groups which increased the wettability of the fabric. In another part of this study, it was found that the atmosphere containing only nitrogen gas showed the most capillary rise to a current of 0.15 A. The results in capillary yarns and fabrics showed that the thread reached equilibrium in a time much less than the fabric to an atmosphere of 100% nitrogen and 0.15 A. Current Plasma technology was effective to increase the hydrophilicity of PLA fabric, providing surface characteristics favorable for future application in the biomedical field